On Sin and Sacrifice: How Intrinsic Religiosity and Sexual-Guilt Create Support for Martyrdom - Belanger, Jocelyn J.; Kruglanski, Arie W.; Kessels, Ursula (Psychological Research on Urban Society, 2019)
The affective, behavioral, and cognitive influence of sexual sin is investigated in this research. In Study 1, we demonstrated that religious people watching erotic (vs. neutral) images reported greater sexual guilt, which in turn increased their willingness to self-sacrifice for a cause. Extending these results, in Study 2 we demonstrated that when recalling a time when they had committed a sexual sin (vs. no sin), people with an intrinsic religious orientation believe in a more punishing view of God (akin to the Old Testament), which in turn predicts the extent to which they engaged in painful sacrificial behavior. Overall, these results suggest that sexual sins motivate self-sacrifice to repent, especially among those with an intrinsic (vs. extrinsic) religious orientation.